Comparative efficacies of topical antiseptic eardrops against biofilms from methicillin-resistant Staphylococcus aureus and quinolone-resistant Pseudomonas aeruginosa. Issue 6 (18th June 2018) - Youn, C K; Jun, Y; Jo, E-R; Jang, S-J; Song, H; Cho, S I
Abstract: Objective: The present study aimed to compare the anti-biofilm activities of four commonly available antiseptic eardrops against biofilms from methicillin-resistant Staphylococcus aureus and quinolone-resistant Pseudomonas aeruginosa in vitro . Methods: The anti-biofilm activities of 50 per cent Burow's solution, vinegar with water (1:1), 2 per cent acetic acid solution, and 4 per cent boric acid solution were evaluated using biofilm assays. Additionally, the anti-biofilm activities of the four antiseptic solutions against tympanostomy tube biofilms were compared using a scanning electron microscope. Results: The inhibition of biofilm formation from methicillin-resistant S aureus and quinolone-resistant P aeruginosa occurred after treatment with 4 per cent boric acid solution, 2 per cent acetic acid solution, and vinegar with water (1:1). However, 50 per cent Burow's solution did not exhibit effective anti-biofilm activity. Conclusion: The results indicate that 4 per cent boric acid solution and vinegar with water (1:1) are potent inhibitors of biofilms from methicillin-resistant S aureus and quinolone-resistant P aeruginosa, and provide safe pH levels for avoiding ototoxicity.